The university's social responsibility in protecting women from religious violence: A field study in Mosul - Mahmoud, Enas Mohamed Aziz; Khudair, Mahmoud Khleif (Al-Adab Journal, 2020)
Violence is a form of oppression practiced against a group or group or individuals carried out by a certain party seeking to achieve a goal or principle of principles. Women have historically been part of this violence despite repeated attempts to give them their rights, but they have always suffered from shortcomings. Violation and deprivation of spiritual and social freedom in various societies and the city of Mosul after being subjected to the worst forms of oppression and exclusion and religious and social torture and religious barbarism represented by the culture of violence based on the interpretation of the wrong religion of Islam was a large share of women will try to address the vinegar This research and we provide a hierarchy of images of the abuse suffered by the woman exclusively conductive and lived during that period and left these tribulations on the character and its outlook on life and the role played by the universities in the city of Mosul in the return of this slide and ways of adaptation and psychological harmony within the community and its social responsibility towards him in general and women on In particular, and to provide important results that serve to sensitize, serve and guide the institutions of society and the State, in accordance with their respective fields of competence and scope.